Treating Chronic Migraine With Neuromodulation: The Role of Neurophysiological Abnormalities and Maladaptive Plasticity - Viganò, Alessandro; Toscano, Massimiliano; Puledda, Francesca; Di Piero, Vittorio (Frontiers in Pharmacology, 2019)
Chronic migraine (CM) is the most disabling form of migraine, mostly because pharmacological treatment efficacy is low and side effects are common, leading to poor adherence to pharmacological antimigraine prophylaxis. There is therefore a need of new more effective and more tolerated pharmacological and non-pharmacological therapeutic options. Recent evidences support the hypothesis that neurophysiological abnormalities occurring during migraine chronification entail abnormal LTP phenomena in several brain levels, leading to a plasticity-based neuronal hyperexcitability state. In virtue of its safe profile, Non-Invasive Brain Stimulation (NIBS) in migraine has growing substantially in recent years, allowing to reverse dysplasticity mechanism. NIBS techniques represent a very promising strategy for chronic migraine since it provides the opportunity to induce changes of neural plasticity outlasting the stimulation period by aiming stimulations at the neurophysiological abnormalities that contribute to the transition from episodic to chronic migraine, as central sensitization, interictal habituation deficit, brainstem and thalamic dysfunctions with the concomitant opportunity of avoiding cumbersome medication-related side effects and drug-drug interactions. In the recent years, several techniques (including transcranial magnetic stimulation, transcranial direct current stimulation and vagus nerve stimulation) have been used in chronic migraine prevention targeting different parts of the nervous system with somewhat contrasting results, possibly because of the lack of univocal rationale and montage. To understand the potential of NIBS modulatory effect in chronic migraine, we will firstly review some basic notion of brain plasticity mechanism and describe the role of neural (dys)plasticity in migraine chronification. We collected evidence to support the concept that alterations of the excitatory-inhibitory balance leads to long-term modifications of neural circuits and a hyperexcitability state, through a decrease in the activity of inhibitory synapses (i.e. disinhibition). Besides learning and memory, excitatory-inhibitory balance of neural circuits and networks is also a pivotal mechanism to shape and maintain synapses activity as well as sensory and nociceptive representations. Lastly, we will look at the results of clinical trials that applied neuromodulation in migraine prevention in the light of their possible effect on neural plasticity